Peningkatan Kemampuan Mengecap dengan Media Jari pada Anak Kelompok B TK Pertiwi Gading Kecamatan Tanon Kabupaten Sragen - Ngadiyem, Ngadiyem (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Fingerprint creation is a drawing technique using fingerprints, this activity is very popular for young children, because this activity is like playing activities, but has meaning for children. The formulation of the problem in this research is